Food and Drink: Thoughts on Base Size in Sensory and Consumer Research - Moskowitz, Howard (Edelweiss Applied Science and Technology, 2020)
In the applied world of product testing the appropriate number of panelists (base size) involves technical and business considerations. Base sizes range from very low (around six; used in expert panelist profiling) to high (hundreds; used in product tests by marketing researchers). Often base sizes are dictated by the requirement that the project identify statistical differences between or among samples. The probabilistic analysis of differences (significance vs. insignificance) derives from statistical theory, with base size used as a method to influence the sampling error (variability). This paper looks at base sizes another way-from the viewpoint of psychophysical scaling. The issue then can be re-stated as ‘what is the necessary base size at which the average rating stabilizes?’ Empirical data suggest that base sizes of 40-50 panelists generate stable averages and that beyond the 80 panelists the average is not particularly affected by the base size. These results hold for actual data for a variety of products, and for different types of attributes, specifically sensory (amount of a characteristic), and hedonic (liking of a characteristic).